Value of passive immune hemolysis for detection of heat-labile enterotoxin produced by enterotoxigenic Escherichia coli. - Tsukamoto, T (1980)
The method of passive immune hemolysis of Evans and Evans (Infect. Immun. 16:604-609, 1977) for detection of heat-labile enterotoxin produced by enterotoxigenic Escherichia coli was modified. A total of 373 strains of E. coli were tested by this method using materials obtained by treating the cells with polymyxin B and rabbit antiserum against cholera enterotoxin, purified by affinity gel column coupled with purified cholera enterotoxin, in N-hydroxyethylpiperazine-N'-2-ethanesulfonic acid buffer (pH 6.7). The results correlated very well with those obtained in an assay with Chinese hamster ovary cells. It is concluded that passive immune hemolysis is useful as a routine clinical method for identifying E. coli strains that produce heat-labile enterotoxin.